Chlamydia pneumoniae infection of lungs and macrophages indirectly stimulates the phenotypic conversion of smooth muscle cells and mesenchymal stem cells: potential roles in vascular calcification and fibrosis - Cabbage, Sarah; Ieronimakis, Nicholas; Preusch, Michael; Lee, Amy; Ricks, Jerry; Janebodin, Kajohnkiart; Hays, Aislinn; Wijelath, Errol S.; Reyes, Morayma; Campbell, Lee Ann; Rosenfeld, Michael E. (Pathogens and disease, 2014)
Pseudomonas aeruginosa is equipped with a large arsenal of cell associated and secreted virulence factors and can use them together to enhance its own virulence